U–Pb detrital zircon dating applied to metavolcano-sedimentary complexes of the São Gabriel Terrane: New constraints on the evolution of the Dom Feliciano Belt. (October 2021) - Philipp, R.P.; Pimentel, M.M.; Basei, M.A.S.; Salvi, M.; De Lena, L.O.F.; Vedana, L.A.; Gubert, M.L.; Lopes, C.G.; Laux, J.H.; Camozzato, E.
Abstract: The Tonian to Cryogenian São Gabriel Terrane located at the northwestern portion of Dom Feliciano Belt, in southern Brazil, provides sedimentation and magmatism records associated with the Rodinia supercontinent and its subsequent deformation and metamorphism during the West Gondwana assembly. It is composed by a succession of arc-related associations including metavolcano-sedimentary and orthogneisses complexes, accretionary prism associations with mafic-ultramafic complexes (ophiolites) and passive margin metasedimentary associations. New U–Pb analyses by LA-ICPMS on detrital zircon from the supracrustal metamorphic complexes in its type-area indicate two distinct times of deposition, sources and tectonic settings. Arc-related complexes occur as parallel bodies interleaved with the metaplutonic associations- of the Passinho (0.9–0.85 Ga) and São Gabriel (0.78–0.72 Ga) arcs. These complexes have detrital zircon data ranging between 0.94 and 0.70 Ga and depositional age constrained at 0.68 Ga. Passive margin complexes constitute a long and continuous belt located at the eastern and southern borders of the São Gabriel Terrane and were deposited over the Paleoproterozoic basement. These complexes show a wide range of detrital zircon ages, between 3.6–1.62 Ga, and a maximum depositional age of 1.58 Ga. The regional mixed sources and the geological context are consistent with accumulation in a passive margin basin situated on the border of an ancient continental plate represented by the Rio de la Plata Craton. Metamorphic zircon overgrowths indicate that the arc-related complexes were accreted during a Cryogenian (0.71–0.70 Ga) collisional event. The contact between the São Gabriel Terrane and the Paleoproterozoic basement units located to the east and south is tectonic. The distinct geological and geophysical features of this boundary characterize it as a suture zone and emphasize its allochthonous and exotic character. Graphical abstract: Image 1 Highlights: U–Pb zircon data of the supracrustal metamorphic complexes of the São Gabriel Terrane. Two detrital zircons groups: 3.6–1.5 Ga (passive margin) and 0.96–0.70 Ga (arc-related). Two distinct associations of supracrustal metamorphic complexes. Older mature siliciclastic and carbonatic association. Neoproterozoic immature metasediments and metavolcanics rocks. Two main source areas: Rio de la Plata Craton-Nico Perez Terrane and Tonian-Passinho and São Gabriel arcs. Rodinia fragmentation in the SW portion of Gondwana.